Open innovation business model as an opportunity to enhance the development of sustainable shared mobility industry - Katarzyna Turoń (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The shared mobility services market is growing and changing very rapidly. Many novelties are introduced to the systems, ranging from improvements to the services already offered to services referred to as innovative. Since the following years are to bring significant development of mobility as a service (MaaS) systems, data sharing, and cooperation on the mobility market, the article is dedicated to check whether the current business models of the industry are ready for the open innovations implementations. The article aimed to analyze the business models of shared mobility systems along with their presentation in the form of CANVAS models and to investigate whether the models contain aspects of open innovation. Moreover, the article presents its own value-added open business model prepared for the whole shared mobility market. The paper also identifies a set of open innovations that can be implemented by all types of shared mobility operators. It proposed the basis that operators can use when developing their own open business models. The developed research is an original contribution to filling the research gap concerning the approach to open innovation by operators of all types of shared mobility services available on the market. The results show that car-sharing service providers are the biggest opponents of open innovation. On the other hand, the most 'open' systems are bike-sharing services. The conducted research may support operators in the process of transforming their businesses into more accessible for users. It also helps to develop the open innovation concept to create more sustainable shared mobility systems along the lines of collaborative economy assumptions.
Keywords: 650; shared mobility; collaborative economy; open innovation; business models; data sharing; transportation engineering; mobility management; open shared mobility systems; sustainable transport systems